Pengenalan Aplikasi Plaxis 2D Versi 2023 bagi Komunitas Literasi Muda Teknik Sipil Pekanbaru - Anggraini, Muthia; Trisep Haris, Virgo (Jurnal Pengabdian KOLABORATIF, 2025)
Global developments encourage the education sector to continuously prepare itself with technological developments to improve the quality of education and enhance human resource capabilities. Quality improvement must be accompanied by mastery of information and communication technology. Technological developments in the field of infrastructure or development in civil engineering include geotechnics. Plaxis is one application in the geotechnics field, namely a computer program based on finite element method calculations that can be used for deformation and stability analysis. The condition of partners who are members of the young civil engineering literacy in Pekanbaru still many do not understand and are not even familiar with this Plaxis application. The purpose of this activity is to introduce the basics of the Plaxis 2D application version 2023 to partners. This training method is through lectures and direct practice that includes the preparation stage, the implementation stage, and the evaluation stage. The location of the service is at the Pekanbaru College of Technology. As a result, the understanding of training participants increased by 53.33% - 78.57% after the Plaxis 2D version 2023 training was carried out.